Self‐Reconstructed Spinel Surface Structure Enabling the Long‐Term Stable Hydrogen Evolution Reaction/Oxygen Evolution Reaction Efficiency of FeCoNiRu High‐Entropy Alloyed Electrocatalyst - Huang, Kang; Xia, Jiuyang; Lu, Yu; Zhang, Bowei; Shi, Wencong; Cao, Xun; Zhang, Xinyue; Woods, Lilia M.; Han, Changcun; Chen, Chunjin; Wang, Tian; Wu, Junsheng; et al. (Advanced science, 2023)
High catalytic efficiency and long‐term stability are two main components for the performance assessment of an electrocatalyst. Previous attention has been paid more to efficiency other than stability. The present work is focused on the study of the stability processed on the FeCoNiRu high‐entropy alloy (HEA) in correlation with its catalytic efficiency. This catalyst has demonstrated not only performing the simultaneous hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) with high efficiency but also sustaining long‐term stability upon HER and OER. The study reveals that the outstanding stability is attributed to the spinel oxide surface layer developed during evolution reactions. The spinel structure preserves the active sites that are inherited from the HEA's intrinsic structure. This work will provide an insightful direction/pathway for the design and manufacturing activities of other metallic electrocatalysts and a benchmark for the assessment of their efficiency–stability relationship. The stability of electrocatalysts is correlated with their surface structures that are self‐reconstructed responding to the hydrogen evolution reaction (HER) or oxygen evolution reaction (OER). The spinel oxide, inherited from the original high‐entropy alloy catalyst and developed over the surface of FeCoNiRu when subject to the polarization, provides the hollow active sites enabling the long‐term stabilities of HER and OER.